Słowo i tekst w komunikacji przekładowej (na materiale rosyjskich tekstów prasowych w przekładzie na język polski) - Pstyga, Alicja (Видавництво Львівської політехніки, 2015)
This paper deals with one of the aspects of contemporary communication: media discourse which involves translation in view of the selection of thier equivalents in the translation of Russian press articles into Polish. Translation perspective allows to present word, text and culture relationship in more complex way – as a cross-cultural communication. It indicates two communities as far language and interpretation is concerned and emphasies exceptional dimension of cultural context as well. Presented material leads to a conclusion that translator’s creativity is inscribed in the scope of translation which consists faithfulness, correctness and the necessity of making the translation attractive to the reader.
Keywords: communication; interpretation; translation; equivalents; text